On the first direct observation of de-twinning in a twinning-induced plasticity steel. (1st September 2018) - McCormack, Scott J.; Wen, Wei; Pereloma, Elena V.; Tomé, Carlos N.; Gazder, Azdiar A.; Saleh, Ahmed A.
Abstract: Electron back-scattering diffraction was used to track the microstructure evolution of a fully annealed Fe-24Mn-3Al-2Si-1Ni-0.06C TWinning Induced Plasticity (TWIP) steel during interrupted reverse (tension-compression) loading. Direct observation of the same selected area revealed that all deformation twins formed during forward tension loading (0.128 true strain) were removed upon subsequent reverse compression loading (0.031 true strain). Consequently, the present study provides the first unambiguous experimental evidence of de-twinning during the reverse loading of a polycrystalline TWIP steel. The reverse loading behaviour was simulated by a dislocation-based hardening model embedded in the Visco-Plastic Self-Consistent (VPSC) polycrystal framework taking into account the accumulation and annihilation of dislocations and back-stress effects. The model has been extended to account for the processes of twinning and de-twinning, as well as the twin barrier effect under load reversal. A new formulation based on the changes in the dislocation mean free path is proposed to track twin lamellae generation/annihilation throughout deformation along with its associated effect on hardening. Graphical abstract: Image 1